الآليات القانونية لضمان الثقة في مجال المعاملات الإلكترونية - الزهره بره (My University, 2022)
أدى التطور التكنولوجي الذي نعيشه الآن، والذي يطلق عليه عصر الثورة المعلومات والبيانات إلى ظهور وسائل وأساليب جيهة في التعامل لم تكن معروفة منذ سنوات قليلة ساهمت هذه الوسائل في سرعة وسهولة الحصول على المعلومة ونشرها بعض النظر عن بعدها الجغرافي فالعالم بأسرة يعيش اليوم على وقع ثورة حقيقة المعلومات في مختلف الميادي، بحيث ساهم تبلي كنولوجيا المعلومات في تجاوز الحدود المكانية والزمانية والتخلص من الحوامل المادية، وهي بلا تلك تحولات عطرية وصيفة مثلت سعرها في تاريخ البشرية ونقلة نوعية في سلوكيات الأفراد والجماعات، أسست إلى خلق قواعد جديدة في التعامل تنذر بالتراب نهاية عصر الأوراق واستبداله بعصر الرقمية رهم ايجابة هذه التكنولوها ووسائلها الفنية المنظورة والمارها المنامة في مختلف المجالات، إلا أنها كارت العديد من المشكلات القانونية خاصة في مجال المبات التصرفات التي تعرى عبر وسائل الاتصال الحديثة والتوثق من محتواها، ومن صدورها من نسبت إليه دون تحريف أو تعديل أو تغير وذلك لأنها تقدم في بيئة التراضية وبين الطراف لا تربطهم علاقة قانونية مسبقة، ولا تجمعهم مجلس واحد، وقد لا يعرف بعضهم الآخر، بالإضافة إلى العقار هذه التصرفات العنصري الأمن والسرية نتيجة أعمال القرصنة والخالات عبر المشروعة التي التعريض لها، مما ربع الطباعا بأن الوسائل الإلكترونية عديمة اللغة. النتيجة لذلك كل الك من إحاطة هذا النوع من التعاملات عصاية فعالة لضمان تحديد هوية المتعافين وحقيقة التعامل ومضمونة من جهة، والمحافظة على حرمة الحياة الخاصة وتكريس منية انتقال المعلومات من جهة أخرى. ولما كان القانون جرأة الواقع كان الله المشرعين من مواكبة المستحات التكنولوجية وخلق البيئة الإلكترونية اللازمة الاستيعابها عن طريق إصدار تشريعات دولية ووطنية تعالج ما استحدث من وسائل وأساليب الإلزام العقود والتوقيع عليها بما يناسب الوسائط الإلكترونية التي تتم من خلالها، وقد حاول المشرع الجزائري اللحاق بالركب والتصدي للانتقادات الموجهة إليه نتيجة تأخره في هذا المجال، وكان ذلك من خلال تعديل الواحد الإلمات والاعتراف بوسائل الإثبات الالكتروني بموجب القانون رقم 05-11 المعدل والمنظم القانون المداني المو مستور المرسوم التنفيذي رقم 07-102 الذي اجمع نشاط التصديق الإلكتروني إلى عظام الترخيص الذي السلامة سلطة ضبط البريد والاتصالات الملكية واللاسلكية، وفي نفس الإطار صدر القانون رقم 15-04 المحدد للقواعد العامة المتعلقة بالتوقيع والتصديق الإلكترونيين، ليتم فيما بعد التدعيم النصوص القانونية المتعلقة بالمعاملات الإلكترونية بموجب القانون رقم 15-05 المتعلق بالتجارة الالكترونية من خلال هذه الصوص القانونية كريم المشرع الجزائري عدة آليات قانونية بهدف ضمان سلامة المبادلات الإلكترونية وتحقيق اللغة والأمان لدى المتعاملين عبر الشبكة المعلوماتية في خدمتها الاعتماد على التوقيع الإلكتروني كاليه الإثبات المعاملات الالكترونية حيث تكمن أهمية هذه التقنية في زيادة مستوى الأمن والخصوصية في التعاملات، وقدرتها على حفظ سرية المعلومات والمراسلات بحيث لا يستطيع أي شخص أخر الاطلاع عليها أو تعديلها أو تعريفها، كما يمكنها أن تقدد الشخصية وهوية المرسل والمستقبل الكترونيا للتأكد من مصداقية شخصيتهما مما يسمح يكثف أي تعال أو تلاعب في هذا المجال، من جهة أخرى ثم اللجوء إلى أطراف معاينة قصد توثيق المعاملات الإلكترونية، وذلك عن طريق اعتماد آلية التصديق الإلكتروني التي تعمل على خلق بيئة الكترونية آمنة للتعامل عبر شبكة المعلومات الجهات التصديق الإلكتروني تقوم بدور الوسيط المؤتمن بين المتعاملين في المبادلات الالكترونية، مؤكد هوية الأطراف وتعدد أهليتهم للتعامل كما تضمن سلامة محتوى البيانات المناولة عبر الشبكة، وتصدر شهادات سديق الكترونية التوثيقها. The technological advancements we are currently experiencing, often referred to as the information and data revolution, have led to the emergence of new methods and approaches to communication that were unknown just a few years ago. These methods have contributed to the speed and ease of accessing and disseminating information, regardless of geographical distance. The entire world is now experiencing a true information revolution across various fields. The development of information technology has transcended spatial and temporal boundaries and eliminated physical media. These are profound and transformative shifts that have marked a turning point in human history and a qualitative leap in the behavior of individuals and groups. They have established new rules of engagement, heralding the end of the paper age and its replacement by the digital age. While these technologies and their visible and tangible applications are undeniable in various fields, they have also created numerous legal problems, particularly in the area of ​​transactions conducted through modern communication methods. Verifying the content and attribution of these transactions to their rightful owners without distortion, alteration, or change is crucial because they occur within a consensual environment between parties who have no prior legal relationship, do not meet in the same place, and may not even know each other. Furthermore, these transactions, especially those involving real estate, raise significant legal issues. The security and confidentiality of cybercrimes and other illicit activities are compromised, leading to the perception that electronic means are languageless. Consequently, all efforts to regulate this type of interaction are crucial to ensure the identification of users, the authenticity of the transaction, and its security, while simultaneously protecting privacy and safeguarding the confidentiality of information transfer. Given that the law reflects reality, legislators have been compelled to keep pace with technological advancements and create the necessary electronic environment to accommodate them. This has been achieved through the issuance of international and national legislation addressing the newly introduced means and methods of contract enforcement and signing, adapting them to the electronic media through which they are conducted. The Algerian legislator has attempted to catch up and address criticisms leveled against it for its perceived lag in this area. This was accomplished through amending the Civil Code and recognizing electronic means of proof under Law No. 05-11, which amended and regulated the Civil Code, and Executive Decree No. 07-102, which consolidated the activity of electronic certification under the authority of the Postal and Telecommunications Regulatory Authority. Within the same framework, Law No. 15-04 was issued, defining the general rules relating to electronic signatures and certification. Subsequently, the legal texts related to electronic transactions were strengthened by Law No. 15-05 concerning electronic commerce. Through these legal texts, the Algerian legislator has provided several legal mechanisms aimed at ensuring the security of electronic exchanges and achieving security and privacy for users of information networks, relying on signatures in their service. Electronic authentication is the means of proving electronic transactions. The importance of this technology lies in increasing the level of security and privacy in transactions, and its ability to preserve the confidentiality of information and correspondence, preventing any unauthorized access, modification, or identification. It can also electronically verify the identity of the sender and receiver to ensure their authenticity, thus minimizing any fraud or manipulation in this area. Furthermore, it allows for the use of third parties to authenticate electronic transactions through the adoption of an electronic authentication mechanism. This mechanism creates a secure electronic environment for transactions over the information network. Electronic authentication bodies act as trusted intermediaries between parties in electronic exchanges, confirming the identity of the parties and their legal capacity to transact. They also ensure the integrity of the data transmitted over the network and issue electronic authentication certificates.
Keywords: التوقيع الإلكتروني، التصديق الإلكتروني، الإثبات الإلكتروني، المعاملات الإلكترونية، التجارة الإلكترونية، الأمن المعلوماتي، التشريع الجزائري.; Electronic signature; electronic authentication; electronic proof; electronic transactions; e-commerce; information security; Algerian legislation.